Difference of co-extracted electron current and beam acceleration in a negative ion source with hydrogen-isotope ions. Issue 1 (1st April 2022) - Ikeda, K.; Tsumori, K.; Nakano, H.; Nagaoka, K.; Takeiri, Y.; Masaki, S.; Rattanawongnara, E.; Osakabe, M.
Abstract: Improvement of the performance on a hydrogen/deuterium negative ion source for a nuclear fusion device is reported. In particular, the suppression of the co-extracted electron current, Ie, is an important issue to ensure the stable beam acceleration. Improvement of the Ie has been confirmed by optimizing the magnetic field of the electron deflection magnet in the extraction grid. Two other new methods for reduction of the Ie were validated. The first was an electron fence whose rods were set between the rows of apertures on a plasma grid. The electron and negative ion current ratio, approximately Ie /I acc, was greatly improved from 0.7 to 0.25 in deuterium. The second was an outer iron yoke which enhanced the magnetic flux density 19% inside the arc discharge chamber. The Ie /Iacc using the outer yoke decreased by 0.1 compared with using a normal magnetic filter in a deuterium operation. These attempts have improved the total deuterium injection beam power of 8.4 MW by three negative ion based NBIs.